2007
DOI: 10.1110/ps.062704507
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range side‐chain–main‐chain interactions play crucial roles in stabilizing the (βα)8 barrel motif of the alpha subunit of tryptophan synthase

Abstract: The role of hither-to-fore unrecognized long-range hydrogen bonds between main-chain amide hydrogens and polar side chains on the stability of a well-studied (ba) 8 , TIM barrel protein, the alpha subunit of tryptophan synthase (aTS), was probed by mutational analysis. The F19-D46 and I97-D124 hydrogen bonds link the N terminus of a b-strand with the C terminus of the succeeding antiparallel ahelix, and the A103-D130 hydrogen bond links the N terminus of an a-helix with the C terminus of the succeeding antipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The absence of the βα-hairpin clamps in the I states of all three TIM barrel proteins demonstrates that the potent effects of these clamps only appear as the N state appears [6]. Kinetic folding studies on αTS revealed further that each clamp is crucial for accessing the transition state ensemble required to reach the properly-folded structure [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The absence of the βα-hairpin clamps in the I states of all three TIM barrel proteins demonstrates that the potent effects of these clamps only appear as the N state appears [6]. Kinetic folding studies on αTS revealed further that each clamp is crucial for accessing the transition state ensemble required to reach the properly-folded structure [6].…”
Section: Discussionmentioning
confidence: 98%
“…Kinetic folding studies on αTS revealed further that each clamp is crucial for accessing the transition state ensemble required to reach the properly-folded structure [6]. Although the local connectivity of the βαβ modules might have been expected to enable the clamp to have a role in the early stages of the folding reaction, the primary role of the potent set of clamps is to drive the final stage of the reaction to completion and fully develop global cooperativity.…”
Section: Discussionmentioning
confidence: 99%
“…37 A survey of 71 (βα) 8 barrels revealed a 4-fold symmetry in the preferred locations of these βα-hairpin clamps, and mutagenesis demonstrated their importance for stabilizing both αTS and IGPS. 37,38 The structure of PRAI 26 reveals a canonical βα-hairpin clamp, between the main chain amide hydrogen of Ile355 and a side chain oxygen of Asp374. This interaction secures the N-terminus of strand β 5 to the loop that immediately precedes strand β 6 .…”
Section: Subtle Structural Changes Disfavor Multimerizationmentioning
confidence: 99%
“…The possibility of misfolding at the periphery of an N-terminal core is supported by the results of another mutational analysis of a pair of long-range H-bonds in the N-terminal region between aspartic acid side chains at the C-termini of two helices and main chain amide hydrogens near the N-termini of their preceding β-strands. 56 These βα-hairpin clamps are disrupted in the I1 intermediate. However, the very strong protection of these amide hydrogens against exchange, > weeks-months at pH 7.8 and 25 °C, implies that both have found alternative partners in the I1 state and only exchange through other very high energy intermediates.…”
Section: Why Are the On-and Off-pathway Intermediates For (βα) 8 Barrmentioning
confidence: 99%